Peran Program RW Siaga Dalam Meminimalisir Pandemi Covid-19 Di Kampung Lebak Kantin Kelurahan Sempur: Pemahaman Komunikasi Penyuluhan Dalam Implementasi Pada Program Pemerintah - Soelistyowati , Dinar (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
The purpose of implementing this Community Service activity is to provide counseling to the community to increase understanding of the benefits of having RW Siaga in each area, especially in the Sempur sub-district, Bogor. This counseling emphasized the importance of effective communication in the implementation of RW Siaga programs that must be carried out by the community in order to minimize the increase in Covid-19 cases in each region. To achieve a resilient community in the face of disasters, a supporting factor is needed, namely social capital. Social capital is one of the important factors in building a strong society, where it is an individual ability in relation to other people in a community based on norms and mutual trust to achieve common goals. For this reason, the government has taken the initiative to create RW Siaga in each region so that the community is more orderly in implementing Prokes. This outreach activity has been carried out in August 2021, through a webinar.